2015
DOI: 10.1186/s13293-015-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the brain: a whole body perspective

Abstract: Most writing on sexual differentiation of the mammalian brain (including our own) considers just two organs: the gonads and the brain. This perspective, which leaves out all other body parts, misleads us in several ways. First, there is accumulating evidence that all organs are sexually differentiated, and that sex differences in peripheral organs affect the brain. We demonstrate this by reviewing examples involving sex differences in muscles, adipose tissue, the liver, immune system, gut, kidneys, bladder, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(60 citation statements)
references
References 174 publications
(162 reference statements)
2
57
0
1
Order By: Relevance
“…This approach allows for examination of the common obesityrelated T2D and for a wide significance of the results. The subjects were all female, and findings may therefore not automatically be applied to male subjects (48). However, we have previously compared insulin signaling in adipocytes from female and male subjects, normally and in diabetes, and found no significant differences (46).…”
Section: Methodsmentioning
confidence: 99%
“…This approach allows for examination of the common obesityrelated T2D and for a wide significance of the results. The subjects were all female, and findings may therefore not automatically be applied to male subjects (48). However, we have previously compared insulin signaling in adipocytes from female and male subjects, normally and in diabetes, and found no significant differences (46).…”
Section: Methodsmentioning
confidence: 99%
“…De Vries emphasized the importance of the principle of 'compensation' in considering the functionality of a variety of sex effects [59][60][61]. He and others refer to compensatory sex-dependent processes that act to reduce rather than create differences between females and males.…”
Section: Sex and Brain Functionmentioning
confidence: 99%
“…Yet, when scientists and laypeople list differences between females and males in the brain, they often implicitly assume that the more differences there are, the more different are the two sex categories, ignoring the possibility that somepossibly many-differences may compensate for others (for review and examples see [59][60][61]; see [62] for a detailed example of compensation in the dopaminergic system and [63] for similar considerations in the case of sex effects on gene networks).…”
Section: Sex and Brain Functionmentioning
confidence: 99%
“…The work of these authors was carried out with the same strain of mice (ICR) but they were male animals; even so, the distribution of proteins was similar to that found in females. Currently there are researchers who emphasize confirming neurohistological and neurochemical findings in both sexes because sexual dimorphism has been found in different areas of the nervous system including OB (de Vries & Forger, 2015). Other authors have confirmed the immunoreactivity of CB in the glomerular stratum (Kosaka & Kosaka, 2004) Table II.…”
Section: Discussionmentioning
confidence: 78%